Scare School Diaries : Welcome to Scare School - Book 1 - Lerner, Jarrett (New York : Aladdin, 2024)
Bash is a young ghost who has never been good at scaring people is nervous about his first day at scare school, where he will learn to master the necessary skills to become a successful ghost.
Keywords: Ghost stories; Fear of failure -- Juvenile fiction; First day of school -- Juvenile fiction; Schools -- Juvenile fiction; Ghosts -- Fiction; Fear -- Fiction; First day of school -- Fiction; Schools -- Fiction; School fiction